The Master of Library Science graduates of the Institute of Library Science, University of the Philippines, AY 1981-1992 a follow-up study - Robles, Ma. Narea S. (Institute of Library Science, University of the Philippines Diliman, 1995)
This study sought to determine the status of the 168 Master of Library Science graduates of the Institute of Library Science for the period AY 1980-81 to AY 1991-92 and to compare the results with those of Corazon Monroy's study. This will give a broad picture of the MLS graduates from 1966 to 1992. It is also the aim of the study to find out what types of positions the MLS graduates are holding and what effect the MLS degree program has had on their careers. Moreover, it tries to ascertain what courses taken by these graduates are considered useful or least useful in the performance of their responsibilities.